The origin of financial crises : central banks, credit bubbles and the efficient market fallacy - Cooper, George (New York : Vintage Books, 2008)
In a series of disarmingly simple arguments, the writer challenges the core principles of today$1 (Bs economic orthodoxy and explains how we have pushed our economy into crisis. He also adds a compelling analysis of the forces behind economic crises. s
Includes bibliographical references and index.
nmn 17/05/13
Loans
Keywords: Financial crises; Efficient market theory; Banks and banking, Central; Monetary policy